2017
DOI: 10.1556/650.2017.30792
|View full text |Cite
|
Sign up to set email alerts
|

A kézhigiénés technika vizsgálata elektronikus ellenőrző berendezés segítségével 26 magyarországi betegellátó intézményben

Abstract: Bevezetés: A helyes kézhigiéné jelentőségét nem lehet vitatni. Semmelweis óta tudjuk, hogy a kézhigiéné a kórházi fertőzések megelőzésének egyik leghatékonyabb módja, amelynek fejlesztésére az oktatás, az ellenőrzés és a visszacsatolás módszere javasolt. Célkitűzés: A modern oktatási eszközök, digitális demonstráló és ellenőrző eszközök hatékonyságának felmérése a széles körű alkalmazásuk során. Módszer: Az általunk szervezett kézhigiénés továbbképzéseken 1269 egészségügyi szakdolgozó vett részt, amelynek kere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Based on observations of future schoolbased health and hygiene education programs should include strategies for involving family members, particularly mothers and siblings. This is in accordance with research conducted by (Lehotsky Á, 2017) which states that the results of the study at the average age of participants were 13.4 years, only 3% of students met the requirements for washing hands. The Centers for Disease Control and Prevention definition, which includes always washing your hands for at least 20 seconds when entering someone's home and after blowing your nose, coughing, and other critical episodes of germ contamination.…”
Section: Discussionsupporting
confidence: 91%
“…Based on observations of future schoolbased health and hygiene education programs should include strategies for involving family members, particularly mothers and siblings. This is in accordance with research conducted by (Lehotsky Á, 2017) which states that the results of the study at the average age of participants were 13.4 years, only 3% of students met the requirements for washing hands. The Centers for Disease Control and Prevention definition, which includes always washing your hands for at least 20 seconds when entering someone's home and after blowing your nose, coughing, and other critical episodes of germ contamination.…”
Section: Discussionsupporting
confidence: 91%
“…Typically missed areas (thumbs and dorsum) were not different when using the two formulations, suggesting that the same hand hygiene technique was followed in both cases. Several previous studies also found that thumbs and fingertips are the most frequently missed areas , [31,32], which suggests that the personal hand hygiene technique may be inappropriate in many cases.…”
Section: Discussionmentioning
confidence: 95%
“…Even with training, the correct HH technique is a common problem in several scenarios. A study conducted with 1269 professionals showed that 33% of them performed the procedure incorrectly ( 25 ) . The results of present study show an even greater deficit regarding the technique, in which 23% to 46% of the observed HH were not performed with the correct technique, reinforcing the deficiency and showing the need to improve this practice.…”
Section: Discussionmentioning
confidence: 99%